IN VITRO ANTI-ACETYL CHOLINESTERASE AND ANTIOXIDANT ACTIVITY OF SELECTED MALAYSIAN PLANTS - H. Nour, Azhari; Khan, Muhammad; Sulaiman, Ahmad Ziad; Batool, Tahira; H. Nour, ABDURAHMAN; Mumtaz Khan, Muhammad; Kormin, Faridah (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of this study is to discover and identify the potential plant extracts that could be vital against Alzheimer’s disease (AD). It is a neurodegenerative disease affecting the brain. The most promising target for the symptomatic treatment and slowing of AD progression is cholinesterase inhibitors from plants. Â Methods: To evaluate the antioxidant and anti-acetylcholinesterase (AChEI) activities leaves and roots were macerated and refluxed with ethanol extracts, from four medicinal plants, namely; C.asiatica, M.pudica, C.pumila, and L.camara. DPPH and Î²-carotene assays were used to determineÂ antioxidant activity;Â whereas Ellman’s colorimetric method was adopted to quantify AChEIÂ activity. Â Results: The refluxed ethanol extract of M.pudica leaves exhibited the highest AChEIÂ activityÂ (IC50Â =Â 0.047Â mg/ml) and high antioxidant activityÂ (Î²-carotene; IC50Â =Â 0.14Â mg/ml and DPPH; IC50Â =Â 0.012 mg/ml). Â Conclusion: Results reveal that all plant extracts studied possess anti-oxidant properties. Most potent extracts could be a lead to novel antioxidants and acetyl cholinesterase inhibitors, for the treatment of AD. Â Keywords; Alzheimer’s disease (AD); Acetylcholinesterase activity; Antioxidant activity; Î²-carotene; DPPH; Medicinal plants.